Effect of feed restriction on hepatic estradiol metabolism and liver function in cows - ONO, Mamiko (J Vet Med Sci, 2019)
In this study, the effects of restriction feeding on the liver function, hepatic uridine diphosphate glucuronosyltransferase (UGT) activity, hepatic insulin-like growth factor (IGF)-1 mRNA expression and response to high-dose estradiol-17β (E(2)) administration were investigated in non-lactating cows. Cows were assigned to either restricted feeding (30% of total digestible nutrient requirement) or ad libitum feeding of a dent corn-based concentrate and roughage for a 2-week feeding trial (Day 1=day of beginning the feeding trial). On day 14, a high-dose E(2) administration study was carried out to examine plasma E(2) levels as an indicator of hepatic E(2) metabolism. Plasma E(2) concentration in the restricted feeding group was consistently higher after high-dose E(2) administration than in the control group. In addition, indocyanine green half-life value was prolonged by restricted feeding for 13 days, and increased liver triglyceride concentration and decreased liver UGT activity were caused by this restriction over 14 days. Restricted feeding did not affect plasma IGF-1 concentration or hepatic IGF-1 mRNA expression. These results suggest that two weeks of restriction feeding led to accumulation of triglyceride, decreased liver blood flow, and slightly impaired liver function, which in turn slowed down the hepatic metabolism of E(2) without significantly impacting hepatic IGF-1 production.